PENGGUNAAN TEHNIK LET’S TELL A STORY DALAM MENINGKATKAN KETERAMPILAN BERBICARA PADA SISWA KELAS XII SMK NAHDLATUN NASYIIN KADUR - kusyairi kus; M. Khoiri (LP2M Sekolah Tinggi Agama Islam Al Falah ( STAIFA ) Pamekasan, 2022)
Speaking is one of the important aspects that is taught to students because speaking involves students' productive activities in conveying verbal utterances so that it becomes consideration for teachers about the importance of using learning techniques that are fun and not boring, in conclusion speaking skills are skills that must be honed and trained by students. Student.The interest of students at SMK. Nahdlatun Nasyiin Kadur in using the Indonesian language can be said to be low. This is evidenced by the fact that their daily activities still use their first language instead of using Indonesian. Besides that, in storytelling activities students tend to be afraid and nervous, so that it is necessary to use appropriate learning techniques to arouse students' enthusiasm and enthusiasm. Let's tell a story technique can be used as an alternative for effective and modern learning to improve speaking skills.The results of student responses to improving speaking skills using the Let's Tell a Story technique have increased, this is usually evidenced by the let's tell a story technique applied to you making your interest more interested in improving speaking skills.